Tutorial-4

Tutorial-4 - Analysis II Tutorial Solution sketches...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon
Analysis II Tutorial Solution sketches Alexandre Tomberg * 1 February 3, 2011 1.1 We will prove a famous theorem about continuous functions: Theorem 1.1 (Weierstrass’ Approximation Theorem) . Polynomials are dense in ( C ([ a,b ]) , k·k ) , where k f k = max x [ a,b ] | f ( x ) | . Actually, we will concentrate on the following explicit version of this theorem: Theorem 1.2. Let f C ([0 , 1]) and ± > 0 be given. Then there exists a polynomial P s.t. k f - P k < ±. Moreover, P can be chosen in the following concrete way. Set P n ( x ) = n X k =0 f ( k/n ) ± n k ² x k (1 - x ) n - k . Then n 0 > 0 such that for all n n 0 , k P n - f k < ± . Proof. We start with the binomial formula and differentiate it with respect to x . ( x + y ) n = n X k =0 ± n k ² x k y n - k = x ∂x ( x + y ) n = nx ( x + y ) n = n X k =0 k ± n k ² x k y n - k . * Please report any errors and typos to [email protected] All tutorial solutions in one pdf can be found at http://www.cs.mcgill.ca/ ~ atombe2/AnalysisTutorial.pdf . 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Taking y = 1 - x , we obtain nx = n X k =0 k ± n k ² x k (1 - x ) n - k . (1) Similarly, x 2 2 ∂x 2 ( x + y ) n = n ( n - 1) x 2 ( x + y ) n = n X k =0 k ( k - 1) ± n k ² x k y n - k , and n ( n - 1) x 2 = n X k =0 k ( k - 1) ± n k ² x k (1 - x ) n - k . (2) Adding ( 1 ) to ( 2 ), we get n ( n - 1) x 2 + nx = n X k =0 k 2 ± n k ² x k (1 - x ) n - k . Now, let r k ( x ) = ( n k ) x k (1 - x ) n - k . We already know that n X k =0 r k ( x ) = 1 n X k =0 kr k ( x ) = nx n X k =0 k 2 r k ( x ) = n ( n - 1) x 2 + nx. Consider n X k =0 ( k - nx ) 2 r k ( x ) = n X k =0 k 2 r k ( x ) - 2 nx n X k =0 kr k ( x ) + n 2 x 2 n X k =0 r k ( x ) = n ( n - 1) x 2 + nx - 2 n 2 x 2 + n 2 x 2 = nx - nx 2 = nx (1 - x ) . Recall that we defined P n ( x ) = n X k =0 f ( k/n ) ± n k ² x k (1 - x ) n - k = n X k =0 f ( k/n ) r k ( x ) . (3) And obviously, f ( x ) = f ( x ) n X k =0 r k ( x ) = n X k =0 f ( x ) r k ( x ) (4) 2
Background image of page 2
Now, since f C ([0 , 1]), f
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 4
This is the end of the preview. Sign up to access the rest of the document.

This document was uploaded on 02/22/2011.

Page1 / 6

Tutorial-4 - Analysis II Tutorial Solution sketches...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online